Pelaksanaan Kegiatan Sosialisasi Pemilu Bersama Bawaslu di SMAN 4 Batam - Cindy Lie; Sherly Tan; Elaine Elaine; Otniel Raja Maruli Situmorang; Faradhilla Nursyahda; Gracia Cindy Carlina; Rubin Rubin; Celine Alviora; Mutiara Aprillia Putri Sela; Jihan Fahira; Selvi Natalia; La Ode Candra; Revo Gahindra Herta Ananda; Marliana Marliana; Rahmi Ayunda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
General elections are an important mechanism in modern democracies to elect people's representatives or government officials which are carried out directly, publicly, freely, confidentially, honestly and fairly. General elections allow the whole community to participate in voting and electing leaders they trust as leaders of the country. However, during general elections, there are usually many problems that cause the implementation of these activities to not go smoothly, such as black campaigning, money politics, hate speech, spreading hoax news, abstention, and so on which should be an important concern in holding general elections. In this case, general election socialisation is needed as a process of conveying information in increasing public knowledge, understanding and awareness in the context of general elections. Creating a clean general election certainly requires public understanding and awareness of the dangers and consequences that will arise from various election problems. As an intelligent society must use the right to vote in general elections properly and don't waste your right to vote in selecting candidates for state leaders. This is important to implement in fostering shared awareness in creating democratic and aspirational general elections. Fair, free and transparent general elections are of course important in maintaining the democratic integrity of a country.